PENGARUH MEDIA PEMBELAJARAN DENGAN MENGGUNAKAN APLIKASI QUIZIZZ TERHADAP HASIL BELAJAR MAHASISWA PADA MATA KULIAH MATEMATIKA DISKRIT - Lamlam Patimah; Widianjani Widianjani (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2022)
Learning outcomes become a benchmark in one's success. Choosing the right learning application can make students comfortable and happy in learning. The purpose of this study was to determine the effect of learning media using the quizizz application on student learning outcomes in discrete mathematics courses. The population used in this study were all students of the Faculty of Engineering, Putra Indonesia University. The samples used were students in semesters V A and V B. This research method used the Nonequivalent Control Group Design. To find out the effect of using the quizizz application on student learning outcomes in the fifth semester discrete mathematics course, Faculty of Engineering at Putra Indonesia Cianjur University, several tests were carried out, namely, instrument tests including validity and reliability, analysis prerequisite tests, namely normality, homogeneity, and T test. Based on the results of hypothesis testing are known through the calculation results of Tcount 2.329 > Ttable 2.039 with a confidence level of 95% or α 0.05. It can be concluded that there is a positive influence on the use of the quizizz application on the learning outcomes of Discrete Mathematics fifth semester students at Putra Indonesia University, Cianjur.   Keywords: Quizizz Application, Learning Outcomes